MnxZn (1-x) Fe2O4 powder and preparation method thereof
MnCO3, ZnO and Fe2O3 powders were processed by high-temperature ball milling method to prepare MnxZn(1-x)Fe2O4 powder, which solved the problems of poor tissue structure and narrow absorption band of ferrite powder, and achieved excellent absorption performance and frequency band coverage.
Patent Information
- Application Number
- CN202411751178.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The existing ferrite powder has poor tissue structure, narrow absorption frequency band, large density and poor weather resistance.
The MnCO3, ZnO and Fe2O3 powders were mixed by high-temperature ball milling method, and high-temperature mechanical force chemical treatment was performed to prepare MnxZn(1-x)Fe2O4 powder.
The absorption performance of ferrite powder is significantly improved, the minimum reflection loss of the product reaches -43.8dB, the effective absorption frequency band covers 4.4~8.3GHz, and the synergistic effect of dielectric loss and magnetic loss is improved, enhancing the attenuation ability and impedance matching characteristics.
Smart Images

Figure CN119569127A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ferrite preparation, in particular to a Mn x Zn (1-x) Fe2O4 powder and preparation method thereof. Background Art
[0002] The structure of ferrite is mainly composed of O 2- The position of O 2- The radius of the ferrite is much larger than the radius of the metal ions inside the lattice, and a face-centered cubic structure can be formed at this time. In the face-centered cubic structure of spinel ferrite, there are two magnetic sublattices: tetrahedral (A) and octahedral (B). The distribution of cations at these two positions can significantly affect the structure and electromagnetic properties of ferrite. Therefore, the magnetic behavior of ferrite is determined by the O 2- It is caused by the intermediate AA, AB and BB positions. At the same time, the existence of the two interstitial positions, tetrahedral (A) and octahedral (B), also provides the possibility for ion substitution / doping. Generally speaking, ferrite as an absorbing material has the disadvantages of narrow absorption band, high density and poor weather resistance, and the electromagnetic properties of ferrite are affected by the preparation method and ion doping / substitution. Therefore, it is of great significance to provide a ferrite with excellent electromagnetic and absorbing properties and a preparation method thereof. Summary of the invention
[0003] The present invention aims to provide a Mn x Zn (1-x) Fe2O4 powder and its preparation method are used to solve the technical problems of poor organizational structure, narrow absorption band, high density and poor weather resistance of ferrite powder in the prior art.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a Mn x Zn (1-x) The preparation method of Fe2O4 powder comprises mixing MnCO3, ZnO and Fe2O3 powders, and then subjecting the mixture to high temperature ball milling to obtain Mn x Zn (1-x) Fe2O4 powder;
[0006] The Mn x Zn (1-x) In Fe2O4 powder, x is 0~1.
[0007] Furthermore, the Mn x Zn (1-x)In the Fe2O4 powder, the mass ratio of MnCO3, ZnO and Fe2O3 powder is 0-2:0.1-0.5:1.
[0008] Furthermore, the temperature of the high-temperature ball milling is 575-830° C., the time of the high-temperature ball milling is 8-15 hours, and the ball-to-material ratio of the high-temperature ball milling is 12-18:1.
[0009] Furthermore, the high temperature ball milling is carried out in an inert gas atmosphere;
[0010] The inert gas includes helium or argon.
[0011] The present invention provides a Mn prepared by the above preparation method. x Zn (1-x) Fe2O4 powder.
[0012] Beneficial effects of the present invention:
[0013] The present invention directly adopts a high-temperature mechanochemical method to prepare the oxide raw material, and the product has more excellent wave absorbing performance. When the matching thickness is 4.3 mm, the minimum reflection loss of the sample reaches -43.8 dB.
[0014] The present invention adopts Mn 2+ Replace Zn 2+ Can significantly increase Mn x Zn (1-x) The microwave absorption performance of Fe2O4 powder and Mn 2+ The greater the content, the more obvious the absorption performance of the product. Among them, when x=1, the absorption performance of the product is the best, the minimum reflection loss can reach -54.7dB when the matching thickness is 4.4mm, and the effective absorption band covers 4.4~8.3GHz.
[0015] The Mn prepared by the present invention x Zn (1-x) Multiple reflections and scattering between Fe2O4 particles can amplify dielectric loss and magnetic loss. The synergistic effect of dielectric loss and magnetic loss makes the product have stronger attenuation ability and better impedance matching characteristics, thereby obtaining excellent wave absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The XRD patterns of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1 are shown;
[0017] Figure 2 , Figure 3 , Figure 4 The SEM images of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1 are respectively;
[0018] Figure 5 TEM images and particle size distribution diagrams of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1, (df) TEM and HR-TEM images of S2, (gi) TEM and HR-TEM images of S3, (jl) particle size distribution diagram;
[0019] Figure 6 : is a relationship diagram between the electromagnetic parameters and frequency of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1, wherein a and b are the real part value ε' and the imaginary part value ε", c and d are the real part value μ' and the imaginary part value μ", e and f are the dielectric loss tangent value tanδe and the magnetic loss tangent value tanδm;
[0020] Figure 7 The three-dimensional R L Figure and R at specific thickness L The relationship curve between the frequency and the frequency, where a, b, and c are three-dimensional R L Figure, a1, b1, c1 are the R of the product at a specific matching thickness L The relationship curve between the frequency and
[0021] Figure 8 It is a three-dimensional Cole-Cole plot of three powders, S3, S1 and S2 in Example 3 and Comparative Example 1;
[0022] Fig. 9 The C0-f curves of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1;
[0023] Fig.10 The attenuation coefficient (α) and impedance matching characteristics (Z) of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1 vary with frequency, wherein a is a graph showing the attenuation coefficient (α) varying with frequency, and b is a graph showing the impedance matching characteristics (Z) varying with frequency;
[0024] Fig.11 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) XRD pattern of Fe2O4 powder;
[0025] Fig.12 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) Magnetic hysteresis loop diagram and unit cell crystal structure of Fe2O4 powder, (a) Magnetic hysteresis loop diagram, (b) unit cell crystal structure diagram;
[0026] Fig.13 Mn is obtained from Examples 1 to 6 respectively. x Zn(1-x) The relationship between the electromagnetic parameters of Fe2O4 powder and the frequency, where a and b are the real value of the dielectric constant ε' and the imaginary value of the dielectric constant ε", c and d are the real value of the magnetic permeability μ' and the imaginary value of the magnetic permeability μ";
[0027] Fig.14 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) The relationship between the dielectric loss tangent value tanδe and the magnetic loss tangent value tanδm of Fe2O4 powder and the frequency;
[0028] Fig.15 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) Three-dimensional R of Fe2O4 powder L Figure, where (a) x = 0, (b) x = 0.2, (c) x = 0.4, (d) x = 0.6, (e) x = 0.8, (f) x = 1;
[0029] Fig.16 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) R of Fe2O4 powder at a specific matching thickness L Graphs showing the relationship between x and frequency, where (a) x = 0, (b) x = 0.2, (c) x = 0.4, (d) x = 0.6, (e) x = 0.8, (f) x = 1;
[0030] Fig.17 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) The relationship between the reflection loss, matching thickness and impedance matching characteristics of Fe2O4 powder and frequency;
[0031] Fig.18 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) Cole-Cole curve and C0-f curve of Fe2O4 powder, where a is the Cole-Cole curve and b is the C0-f curve;
[0032] Fig.19 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) A graph showing the relationship between the attenuation coefficient (α) and the impedance matching characteristic (Z) of Fe2O4 powder as a function of frequency, wherein a is a graph showing the relationship between the attenuation coefficient (α) and the frequency, and b is a graph showing the relationship between the impedance matching characteristic (Z) and the frequency. DETAILED DESCRIPTION
[0033] The present invention provides a Mn x Zn (1-x) The preparation method of Fe2O4 powder comprises mixing MnCO3, ZnO and Fe2O3 powders, and then subjecting the mixture to high temperature ball milling to obtain Mn x Zn (1-x) Fe2O4 powder;
[0034] The Mn x Zn (1-x) In Fe2O4 powder, x is 0~1.
[0035] In the present invention, the Mn x Zn (1-x) In the Fe2O4 powder, the mass ratio of MnCO3, ZnO and Fe2O3 powder is 0-2:0.1-0.5:1, preferably 0.2-1.5:0.2-0.4:1, and more preferably 0.4:0.3:1.
[0036] In the present invention, the temperature of the high-temperature ball milling is 575-830°C, preferably 600-800°C, further preferably 650-750°C, and more preferably 700°C. The time of the high-temperature ball milling is 8-15h, preferably 10-13h, and more preferably 12h. The ball-to-material ratio of the high-temperature ball milling is 12-18:1, preferably 14-16h, and more preferably 15h.
[0037] In the present invention, the high-temperature ball milling is carried out in an inert gas atmosphere;
[0038] The inert gas comprises helium or argon, preferably argon.
[0039] The present invention provides a Mn prepared by the above preparation method. x Zn (1-x) Fe2O4 powder.
[0040] In the present invention, the raw materials and reagents used in the sample preparation process are shown in Table 1.
[0041] Table 1 Experimental materials and reagents
[0042] name Chemical formula Specification / Purity Manufacturer Zinc Oxide ZnO Analytical grade Tianjin Damao Chemical Reagent Factory Manganese carbonate <![CDATA[MnCO3]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. Iron (III) oxide <![CDATA[Fe2O3]]> Analytical grade Tianjin Damao Chemical Reagent Factory Manganese sulfate monohydrate <![CDATA[MnSO4·H2O]]> Analytical grade Tianjin Fuchen Chemical Reagent Co., Ltd. Ferrous sulfate heptahydrate <![CDATA[FeSO4·7H2O]]> Analytical grade Tianjin Damao Chemical Reagent Factory Zinc sulfate heptahydrate <![CDATA[ZnSO4·7H2O]]> Analytical grade Tianjin Damao Chemical Reagent Factory Sodium hydroxide NaOH Analytical grade Tianjin Damao Chemical Reagent Factory Argon Ar ≥99.95% Shenyang Kerui Special Gas Co., Ltd. Deionized water <![CDATA[H2O]]> - Laboratory-made
[0043] In the present invention, the equipment used in the experiment and the instruments used to characterize the samples are shown in Table 2.
[0044] Table 2 Experimental equipment and instruments
[0045]
[0046]
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] 159.68 g of Fe2O3 and 25.6 g of ZnO powder were weighed separately and put into a stainless steel ball mill together with zirconium oxide grinding balls. Then 100 g of the mixed powder was ball milled at 700°C and a ball-to-material ratio of 15:1 for 10 hours to obtain ZnFe2O4 powder.
[0050] Example 2
[0051] 159.68g Fe2O3, 31.58g MnCO3 and 65.12g ZnO powders were weighed and put into a stainless steel ball mill together with zirconium oxide grinding balls. Then 100g of the mixed powder was ball milled at 700℃ and a ball-to-material ratio of 15:1 for 10h to obtain MnO. 0.2 Zn 0.8 Fe2O4 powder.
[0052] Example 3
[0053] 83.7 g Fe2O3, 24.2 g MnCO3 and 25.6 g ZnO powders were weighed and placed in a stainless steel ball mill together with zirconium oxide grinding balls. Then 100 g of the mixed powder was ball milled at 700 °C for 10 h with a ball-to-material ratio of 15:1 to obtain MnO. 0.4 Zn 0.6 Fe2O4 powder, denoted as S3.
[0054] Example 4
[0055] 159.68g Fe2O3, 94.73g MnCO3 and 32.56g ZnO powders were weighed and put into a stainless steel ball mill together with zirconium oxide grinding balls. Then 100g of the mixed powder was ball milled at 700℃ and a ball-to-material ratio of 15:1 for 10h to obtain MnO. 0.6 Zn 0.4 Fe2O4 powder.
[0056] Example 5
[0057] 159.68g Fe2O3, 126.3g MnCO3 and 16.28g ZnO powders were weighed and put into a stainless steel ball mill together with zirconium oxide grinding balls. Then 100g of the mixed powder was ball milled at 700℃ and a ball-to-material ratio of 15:1 for 10h to obtain MnO2. 0.8 Zn 0.2Fe2O4 powder.
[0058] Example 6
[0059] 159.68g of Fe2O3 and 157.88g of MnCO3 powder were weighed separately and put into a stainless steel ball mill together with zirconia grinding balls. Then 100g of the mixed powder was ball milled at 700℃ and a ball-to-material ratio of 15:1 for 10 hours to obtain MnFe2O4 powder.
[0060] Comparative Example 1
[0061] 21.9 g ZnSO4·7H2O, 96.1 g FeSO4·7H2O and 14.1 g MnSO4·H2O powders (n(Fe):n(Mn):n(Zn)=1:0.2:0.3) were weighed respectively, and the above powders were dissolved in 2 L deionized water and magnetically stirred for 30 min. After they were fully dissolved, 2 M NaOH solution was added to adjust the pH to pH=10, and then stirred in a water bath at 80°C for 2 h, and then allowed to stand to obtain a dark green colloid. After filtering out the supernatant, the colloid was repeatedly washed with deionized water until neutral, and then centrifuged and dried, and ground into fine powder to obtain a precursor powder, which was marked as S1;
[0062] 100 g of the dried precursor powder was weighed and placed into a stainless steel ball mill together with zirconium oxide grinding balls, followed by high-temperature ball milling for 10 h at 700° C. and a ball-to-material ratio of 15:1. The obtained product was recorded as S2.
[0063] The analysis and testing methods are as follows:
[0064] The samples were analyzed for phase and crystal structure using an X-ray diffraction analyzer (XRD, Cu target Kα ray, scanning rate of 5° / min, scanning angle of 10°-80°). The particle size distribution, morphology and element distribution of the samples were observed using a scanning electron microscope (SEM), a transmission electron microscope (TEM) and an X-ray energy dispersive spectrometer (EDS). The Fourier transform infrared spectrometer (FT-IR, wavelength range of 400 cm -1 -4000cm -1) was used to characterize the material composition of the samples; the elemental composition and chemical state of the samples were characterized by X-ray photoelectron spectroscopy (XPS); the static magnetic properties of the samples at 300K were tested by a vibrating sample magnetometer (the magnetic field range was -30 to 30 kOe); the electromagnetic parameters (ε', ε", μ', μ") of the samples in the frequency range of 2 to 18 GHz were tested by a vector network analyzer (VNA), and then the three-dimensional reflection loss diagram of the samples, the reflection loss value (RL) at different matching thicknesses, the C0 value, the attenuation coefficient (α), the impedance matching coefficient (Z) and the quarter wavelength (λ / 4) curve were calculated by Matlab software.
[0065] Table 3 shows the Mn obtained in Examples 1 to 6. x Zn (1-x) Crystal structure parameters of Fe2O4 powder.
[0066] Table 3Mn x Zn (1-x) Lattice constant (a), unit cell volume (V), particle size (Dxrd), interplanar spacing (dxrd) and lattice strain (η) of Fe2O4 powder
[0067]
[0068] It can be seen from Table 3 that as Mn 2+ As the content increases, the lattice constant increases. This is due to the fact that r(Mn 2+ )>r(Zn 2+ ), when Mn 2+ Replace Zn 2+ When entering the crystal, the unit cell expands and causes lattice distortion, which proves that Mn 2+ Successfully replaced part of the Zn in ZnFe2O4 2+ At the same time, as Mn 2+ With the increase of the content, the lattice strain of the product first decreases and then increases due to the increase of grain size. Table 3 shows that all samples have nanocrystals.
[0069] Table 4 shows Mn x Zn (1-x) Static magnetic properties parameters of Fe2O4 powder.
[0070] Table 4Mn x Zn (1-x) Static magnetic parameters of Fe2O4 powder
[0071] sample <![CDATA[M s (emu / g)]]> <![CDATA[M r (emu / g)]]> <![CDATA[H c (You)]]> <![CDATA[M r / M s ]]> x=0 1.35 0.01 36.89 0.00741 x=0.2 4.50 0.17 8.98 0.03778 x=0.4 17.02 0.19 3.72 0.01116 x=0.6 52.87 1.18 12.93 0.02232 x=0.8 70.45 3.21 41.24 0.04556 x=1 73.02 9.83 105.75 0.14156
[0072] It can be seen from Table 4 that as Mn 2+ The increase in content, M r / Ms gradually increases, indicating that the magnetocrystalline anisotropy increases, H c Value varies with Mn 2+ The content of H increases, but it is still at a low level. c Value and higher M s Under the combined effect of Mn and Mg values, the material has excellent magnetic permeability, thereby improving magnetic loss capacity and optimizing its wave absorption performance. 2+ The increase in Mn content helps to enhance x Zn (1-x) Microwave absorbing properties of Fe2O4 powder.
[0073] Table 5 shows the crystal structure parameters of S3 and S2 powders obtained in Example 3 and Comparative Example 1, respectively.
[0074] Table 5 Crystal structure parameters of S3 and S2 powders obtained in Example 3 and Comparative Example 1 respectively
[0075]
[0076] As shown in Table 5, the lattice constant (α), interplanar spacing (d), full width at half maximum (FWHM), diffraction angle (2θ) and grain size (Dsch) of S2 and S3 are shown. The grain size difference between S2 and S3 is not large, but the lattice constant (8.4709) is about 0.08% higher than that of S3 (8.4641). The difference in lattice constants may cause certain differences in the structures of S2 and S3, resulting in different distributions of metal cations inside the crystal, thus affecting the microwave absorption performance of the product.
[0077] From the above embodiments, it can be seen that the present invention provides a Mn x Zn (1-x) Fe2O4 powder and preparation method thereof. Figure 1 The XRD patterns of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the characteristic peak intensity of S1 is relatively low, indicating that the crystallinity of the precursor obtained by the coprecipitation method is poor, while the crystallinity of S2 and S3 is good, which is pure phase Mn 0.4 Zn 0.6 Fe2O4.
[0078] Figure 2 , Figure 3 and Figure 4 The SEM images of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1; Figure 5The TEM images and particle size distribution diagrams of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1, (d-f) TEM and HR-TEM images of S2, (g-i) TEM and HR-TEM images of S3, and (j-l) particle size distribution diagrams. It can be seen from the figure that the particles of S2 are cubic prism structures, and the S3 powder has a uniform spherical structure, the particle size is about 50-300nm, the average particle size is about 160nm, and both S2 and S3 powders have a certain degree of agglomeration.
[0079] Figure 6 The figure is a relationship between the electromagnetic parameters and frequency of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1, wherein a and b are the real part value ε' and the imaginary part value ε", indicating the stability of the complex dielectric constant of the precursor before and after ball milling. Compared with S1 and S2, S3 exhibits obvious frequency-dependent behavior and stronger dielectric loss capacity; c and d are the real part value μ' and the imaginary part value μ", of the magnetic permeability. Among the three, S3 has both strong dielectric loss and magnetic loss capacity, while the dielectric loss and magnetic loss effects of S1 are both weak, and the dielectric loss capacity of S2 is basically the same as that of S1; e and f are the dielectric loss tangent value tanδe and the magnetic loss tangent value tanδm. In the range of 2 to 18 GHz, tanδe (S3) >tanδe (S2) >tanδe (S1) , indicating that the dielectric loss capacity S3>S2>S1. In addition, S2 has tanδm>tanδe in 2~18GHz, indicating that the loss mechanism of S2 is mainly magnetic loss; S3 has tanδm>tanδe and tanδm<tanδe in 2~8GHz and 8~18GHz, respectively, indicating that the loss mechanism of S3 in 2~8GHz and 8~18GHz is mainly magnetic loss and dielectric loss, respectively.
[0080] Figure 7 The three-dimensional R L Figure and R at specific thickness L The relationship curve between the frequency and the frequency, where a, b, and c are three-dimensional R L Figure, a1, b1, c1 are the R of the product at a specific matching thickness L The relationship between and frequency. Figure 7 It can be seen that the R of S1, S2 and S3 LminThey are -10.9dB, -26.6dB and -43.8dB respectively, and the corresponding matching thicknesses are 9.8mm, 7.6mm and 4.3mm respectively. Among the three samples, S3 exhibits the best wave absorbing performance, with an effective absorption band covering 4.56-7.48GHz. By adjusting the matching thickness, the effective absorption band can be less than -10dB in the range of 2-18GHz. In contrast, according to different matching thicknesses, S2 only exhibits a strong absorption peak in the range of 2-6GHz, while S3 has a strong absorption peak in the range of 2-18GHz.
[0081] Figure 8 It is a three-dimensional Cole-Cole diagram of three kinds of powders S3, S1 and S2 in Example 3 and Comparative Example 1. As can be seen from the figure, the Cole curve of S1 shows a high degree of disorder, indicating that its polarization relaxation process is weak. The Cole curves of S2 and S3 are irregular shapes composed of multiple Debye semicircles in the medium and high frequency bands and the "straight tail" in the low frequency band, indicating that their dielectric loss mechanisms are all composed of multiple dipole polarization relaxation and conduction loss. The difference in the Debye semicircle radius of different samples may be caused by the difference in polarization relaxation intensity. At the same time, under the action of mechanical force during the reaction process, a large number of defects are introduced into the powder, and these defects can be used as polarization centers to produce polarization relaxation under the action of an external alternating electromagnetic field. In addition, the presence and direction of dipoles may be affected by defect concentration and structural anisotropy, and the presence of dipoles will affect the generation of dipole polarization relaxation inside the material, thereby affecting the wave absorbing performance of the product.
[0082] Fig. 9 The C0-f curves of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1. As can be seen from the figure, the C0 of S1 remains basically stable within 2 to 18 GHz, indicating that its magnetic loss mechanism is mainly eddy current loss. For S2 and S3, their C0-f curves decrease with the increase of frequency within 2 to 8 GHz, and remain basically stable with the change of frequency within 8 to 18 GHz, indicating that the magnetic loss mechanisms of S2 and S3 within 2 to 8 GHz and 8 to 18 GHz are mainly natural resonance and eddy current loss, respectively.
[0083] Fig.10 Figure 3 shows the relationship between the attenuation coefficient (α) and the impedance matching characteristic (Z) of the three powders S3, S1 and S2 in Example 3 and Comparative Example 1. It can be seen from Figure 3 that there is an α difference between 2 and 18 GHz. S3 >α S2 >α S1 , indicating that S3 has the strongest electromagnetic wave attenuation ability; as shown in Figure b, the Z value of S3 in the range of 2 to 18 GHz is closer to 1.0, indicating that it has more suitable impedance matching characteristics among all products.
[0084] According to the above analysis, the preparation process has a significant impact on the structure and performance of ferrite. Compared with the process of "preparing the precursor first and then subjecting the precursor to high-temperature mechanochemical action", the product of "directly using oxide as raw material and subjecting it to high-temperature mechanochemical action" has better microwave absorption performance. At the same time, R Lmin In addition, the product under this condition has better electromagnetic wave attenuation ability and electromagnetic impedance matching characteristics among all samples, which provide conditions for obtaining better electromagnetic wave absorption performance.
[0085] Fig.11 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) XRD diagram of Fe2O4 powder. The crystal planes corresponding to each characteristic peak are marked in the figure. It can be seen from the figure that the samples all show spinel structure, and the characteristic peaks are sharp, and there is no impurity peak, indicating that it is pure phase Mn x Zn (1-x) Fe2O4 powder. The strongest peaks of all samples are characteristic peaks at the (311) crystal plane. 2+ With the increase of Mn content x Zn (1-x) The characteristic peaks of Fe2O4 powder tend to move to smaller angles.
[0086] Fig.12 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) Hysteresis loop diagram and unit cell crystal structure of Fe2O4 powder, including (a) hysteresis loop diagram, (b) unit cell crystal structure diagram. It can be seen from the figure that Mn 2+ Substitution of Zn at position A 2+ , which increases the magnetic moment of the A-site sublattice and enhances the superexchange interaction between the AB sites. 2+ As the content of Mn increases, the superexchange interaction between the AB sites becomes stronger and stronger, and the ferromagnetic interaction between the AB site cations gradually becomes dominant. x Zn (1-x) The magnetic properties of Fe2O4 are enhanced.
[0087] Fig.13 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) The relationship between the electromagnetic parameters of Fe2O4 powder and frequency, where a and b are the real part of the dielectric constant ε' and the imaginary part of the dielectric constant ε", the ε' and ε" values of all samples are higher at low frequencies, decrease with increasing frequency, and finally tend to be stable. ε' and ε" increase with increasing x, and both reach the maximum value when x = 1. In the present invention, Mn 2+Replace Zn 2+ Will produce more Fe 2+ , thereby increasing the dielectric constant of the product and enhancing the dielectric loss capacity of the material. The greater the substitution amount, the greater the degree of enhancement. c and d are the real part of the permeability μ' and the imaginary part of the permeability μ". When x = 0, 0.2 and 0.4, the μ' value of the sample in the range of 2 to 18 GHz fluctuates around 1.1, indicating that their magnetic storage capacity is weak. When x = 0.8 and 1.0, the μ' value of the sample increases in the low-frequency range, which indicates that as the Mn in the product increases, the 2+ With the increase of Mn content, the magnetic storage capacity of the sample is improved, which can be attributed to the 2+ Zn 2+ The substitution brings about enhanced magnetic properties of the product.
[0088] Fig.14 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) The dielectric loss tangent value tanδe and the magnetic loss tangent value tanδm of Fe2O4 powder. It can be seen from the figure that when x = 0, 0.2 and 0.4, the tanδe and tanδm values are similar in the range of 2 to 18 GHz, so the loss mechanism of the sample at this time is the synergistic effect of dielectric loss and magnetic loss; when x = 0.6, tanδm>tanδe in the range of 2 to 13 GHz, and the loss mechanism is mainly magnetic loss. In the range of 13 to 18 GHz, tanδe and tanδm are similar, and the loss mechanism is dielectric loss / Synergistic effect of magnetic loss; when x = 0.8, the sample has tanδm>tanδe and tanδm<tanδe in 2-13GHz and 13-18GHz, respectively, indicating that the loss mechanism of the sample is mainly magnetic loss and dielectric loss in this frequency range; and when x = 1, the sample has tanδm>tanδe and tanδm<tanδe in 2-9GHz and 9-18GHz, respectively, indicating that the loss mechanism of the sample is mainly magnetic loss and dielectric loss. In addition, it can be observed that with the increase of x, the corresponding tanδe and tanδm of different samples increase accordingly, indicating that Mn 2+ The introduction of can simultaneously enhance the dielectric loss and magnetic loss capabilities of the sample.
[0089] Fig.15 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) Three-dimensional R of Fe2O4 powder L Figure 1, where (a) x = 0; (b) x = 0.2; (c) x = 0.4; (d) x = 0.6; (e) x = 0.8; (f) x = 1. As can be seen from the figure, as x increases, R Lmin It shows an upward trend. When x=1, R Lminis -54.7dB, and the corresponding matching thickness is only 4.4mm. It can be seen that using Mn 2+ Replace Zn 2+ Can significantly improve Mn x Zn (1-x) Microwave absorbing properties of Fe2O4 powder.
[0090] Fig.16 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) R of Fe2O4 powder at a specific matching thickness L The relationship between the R and frequency curves, (a) x = 0; (b) x = 0.2; (c) x = 0.4; (d) x = 0.6; (e) x = 0.8; (f) x = 1. As can be seen from the figure, with the increase of matching thickness, the R of all samples Lmin All of them move toward the low-frequency direction, indicating that all samples have better microwave absorption performance in the low-frequency band.
[0091] Fig.17 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) The relationship between the reflection loss, matching thickness and impedance matching characteristics of Fe2O4 powder and frequency. It can be seen from the figure that R Lmin The frequency corresponding to the input impedance is the same, but different R Lmin The corresponding matching thickness is also consistent with the t calculated by the quarter-wavelength model. m The values are close, and all R Lmin The values are basically located on the quarter-wavelength model curve obtained by electromagnetic parameters. x Zn (1-x) Fe2O4 powder meets the conditions for phase cancellation effect and excellent wave absorbing performance.
[0092] Fig.18 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) Cole-Cole curve and C0-f curve of Fe2O4 powder, where a is the Cole-Cole curve and b is the C0-f curve. As shown in Figure a, when x = 0, 0.2, 0.4 and 0.6, the Cole curve distribution is irregular and there is no obvious Debye semicircle, indicating that the dielectric loss mechanism of the product at this time is mainly conduction loss; when x = 0.8 and 1, the Cole curve is composed of obvious semicircles and straight lines, indicating that the dielectric loss mechanism of the product at this time is composed of multiple polarization relaxation and conduction loss. The multiple polarization relaxation of the product can be attributed to Mn x Zn (1-x)The synergistic effect of the dipole polarization generated by the free electron pairs inside the Fe2O4 powder and the dipole polarization caused by the interface and structural defects, the existence of these relaxations enhances the electromagnetic wave absorption ability of the product. x Zn (1-x) The ε" distribution of Fe2O4 powder shows that the dielectric loss capacity of the samples with x = 0.8 and 1 is stronger than that of the samples with x = 0, 0.2, 0.4 and 0.6. 2+ The content can improve the dielectric loss performance of the product; as shown in Figure b, when x = 0, 0.2 and 0.4, C0 decreases with the increase of frequency in the range of 2 to 3 GHz, indicating that the magnetic loss mechanism is mainly natural resonance; when it is greater than 3 GHz, C0 tends to be stable, and the magnetic loss mechanism is mainly eddy current loss. When x = 0.6, 0.8 and 1, C0 decreases with the increase of frequency in the range of 2 to 13 GHz, and the magnetic loss mechanism is mainly natural resonance; in the range of 13 to 18 GHz, the C0 value tends to be stable, indicating that the magnetic loss mechanism is mainly eddy current loss.
[0093] Fig.19 Mn is obtained from Examples 1 to 6 respectively. x Zn (1-x) The relationship between the attenuation coefficient (α) and impedance matching characteristics (Z) of Fe2O4 powder and the frequency change curve, where a is the relationship between the attenuation coefficient (α) and the frequency change curve. It can be seen from the figure that as x increases, the α value of the product also increases, indicating that Mn 2+ The greater the content, the stronger the electromagnetic wave attenuation ability of the product. Among them, the sample with x=1 has the largest α value; b is the relationship curve of the impedance matching characteristic (Z) with the frequency. It can be seen from the figure that the Z value of all samples is greater than 0.4, indicating that the reflectivity of the incident electromagnetic wave is low and can effectively enter the absorbing material. Among all samples, the Z value of the sample with x=1 at 6GHz is closer to 1, indicating that MnFe2O4 powder has a more suitable impedance matching characteristic among all products.
[0094] According to the above analysis, the results show that Mn 2+ Replace Zn 2+ Can significantly increase Mn x Zn (1-x) The microwave absorption performance of Fe2O4 powder and Mn 2+ The greater the content, the more obvious the absorption performance of the product. Among them, when x=1, the absorption performance of the product is the best, the minimum reflection loss can reach -54.7dB when the matching thickness is 4.4mm, and the effective absorption band covers 4.4~8.3GHz.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A Mn x Zn (1-x) The method for preparing Fe2O4 powder is characterized in that: MnCO3, ZnO and Fe2O3 powders were mixed and then subjected to high temperature ball milling to obtain Mn x Zn (1-x) Fe2O4 powder; The Mn x Zn (1-x) In Fe2O4 powder, x is 0~1.
2. A Mn according to claim 1 x Zn (1-x) The method for preparing Fe2O4 powder is characterized in that: The Mn x Zn (1-x) In the Fe2O4 powder, the mass ratio of MnCO3, ZnO and Fe2O3 powder is 0-2:0.1-0.5:
1.
3. A Mn according to claim 1 or 2 x Zn (1-x) The method for preparing Fe2O4 powder is characterized in that: The temperature of the high-temperature ball milling is 575-830° C., the time of the high-temperature ball milling is 8-15 hours, and the ball-to-material ratio of the high-temperature ball milling is 12-18:
1.
4. A Mn according to claim 3 x Zn (1-x) The method for preparing Fe2O4 powder is characterized in that: The high temperature ball milling is carried out in an inert gas atmosphere; The inert gas includes helium or argon.
5. Mn prepared by the preparation method according to any one of claims 1 to 4 x Zn (1-x) Fe2O4 powder.